In vitro study on the hypoglycemic potential of Nicotiana tabacum leaf extracts - Mutiu Idowu Kazeem; Semawon Mauton Ogungbe; Gbemisola Morounke Saibu; Oluwaseyi Mayode Aboyade (Bangladesh Pharmacological Society, 2014)
Inhibition of some carbohydrate metabolizing enzymes is one of the modes of action of antihyperglycemic agents. The aim of this study was to investigate the in vitro inhibition of α-amylase and α-glucosidase by extracts of N. tabacum leaf. Powdered leaves were extracted with acetone, ethanol and water, and tested for their ability to inhibit α-amylase from Aspergilus oryzae and α-glucosidase from Saccharomyces cerevisae. The results revealed that aqueous extract of the plant was most effective inhibitor of α-amylase (IC50 5.70 mg/mL) while acetone extract exhibited the best inhibitory potential on α-glucosidase (IC50 4.50 mg/mL). Kinetic studies showed that the mode of inhibition of α-amylase by aqueous extract was non-competitive while that of the acetone extract on α-glucosidase was competitive. The observed inhibitions of α-amylase and α-glucosidase suggest that the leaf extracts of N. tabacum may be useful in the management of Diabetes mellitus, which may due to the presence of phytochemicals.